Recombinant Adenovirus siRNA Knocking Down the Ndufs4 Gene Alleviates Myocardial Apoptosis Induced by Oxidative Stress Injury - Beibei Wang; Jinsheng Zhang; Aijun Xu (Cardiology Research and Practice)
Oxidative stress results in myocardial cell apoptosis and even life-threatening heart failure in myocardial ischemia-reperfusion injury. Specific blocking of the complex I could reduce cell apoptosis. Ndufs4 is a nuclear-encoded subunit of the mitochondrial complex I and participates in the electron transport chain. In this study, we designed and synthesized siRNA sequences knocking down the rat Ndufs4 gene, constructed recombinant adenovirus Ndufs4 siRNA (Ad-Ndufs4 siRNA), and primarily verified the role of Ndufs4 in oxidative stress injury. The results showed that the adenovirus infection rate was about 90%, and Ndufs4 mRNA and protein were decreased by 76.7% and 64.9%, respectively. Furthermore, the flow cytometry assay indicated that the cell apoptosis rate of the Ndufs4 siRNA group was significantly decreased as compared with the H2O2-treated group. In conclusion, we successfully constructed Ndufs4 siRNA recombinant adenovirus; furthermore, the downexpression of the Ndufs4 gene may alleviate H2O2-induced H9c2 cell apoptosis.